The open for business model of the bithorax complex in Drosophila - Maeda, Robert K. (Chromosoma, 2015)
After nearly 30 years of effort, Ed Lewis published his 1978 landmark paper in which he described the analysis of a series of mutations that affect the identity of the segments that form along the anterior-posterior (AP) axis of the fly (Lewis 1978). The mutations behaved in a non-canonical fashion in complementation tests, forming what Ed Lewis called a “pseudo-allelic” series. Because of this, he never thought that the mutations represented segment-specific genes. As all of these mutations were grouped to a particular area of the Drosophila third chromosome, the locus became known of as the bithorax complex (BX-C). One of the key findings of Lewis’ article was that it revealed for the first time, to a wide scientific audience, that there was a remarkable correlation between the order of the segment-specific mutations along the chromosome and the order of the segments they affected along the AP axis. In Ed Lewis’ eyes, the mutants he discovered affected “segment-specific functions” that were sequentially activated along the chromosome as one moves from anterior to posterior along the body axis (the colinearity concept now cited in elementary biology textbooks). The nature of the “segment-specific functions” started to become clear when the BX-C was cloned through the pioneering chromosomal walk initiated in the mid 1980s by the Hogness and Bender laboratories (Bender et al. 1983a; Karch et al. 1985). Through this molecular biology effort, and along with genetic characterizations performed by Gines Morata’s group in Madrid (Sanchez-Herrero et al. 1985) and Robert Whittle’s in Sussex (Tiong et al. 1985), it soon became clear that the whole BX-C encoded only three protein-coding genes (Ubx, abd-A, and Abd-B). Later, immunostaining against the Ubx protein hinted that the segment-specific functions could, in fact, be cis-regulatory elements regulating the expression of the three protein-coding genes. In 1987, Peifer, Karch, and Bender proposed a comprehensive model of the functioning of the BX-C, in which the “segment-specific functions” appear as segment-specific enhancers regulating, Ubx, abd-A, or Abd-B (Peifer et al. 1987). Key to their model was that the segmental address of these enhancers was not an inherent ability of the enhancers themselves, but was determined by the chromosomal location in which they lay. In their view, the sequential activation of the segment-specific functions resulted from the sequential opening of chromatin domains along the chromosome as one moves from anterior to posterior. This model soon became known of as the open for business model. While the open for business model is quite easy to visualize at a conceptual level, molecular evidence to validate this model has been missing for almost 30 years. The recent publication describing the outstanding, joint effort from the Bender and Kingston laboratories now provides the missing proof to support this model (Bowman et al. 2014). The purpose of this article is to review the open for business model and take the reader through the genetic arguments that led to its elaboration.